Quality of Care in the Cirrhotic Patient - Volk, Michael L (Clin Transl Gastroenterol, 2016)
Cirrhosis is a common, complex, chronic condition requiring care by multiple specialists in different locations. Emerging data demonstrates limitations in the quality of care these patients receive—in large part due to the problems with care coordination rather than failures of individual providers. This article will discuss approaches for measuring quality, and provide a step-by-step guide for developing quality improvement programs for this patient population.